1995
DOI: 10.1002/bies.950170616
|View full text |Cite
|
Sign up to set email alerts
|

Cell shape and chromosome partition in prokaryotes or, why E. coli is rod‐shaped and haploid

Abstract: In the rod-shaped cells of E. coli, chromosome segregation takes place immediately after replication has been completed. A septum then forms between the two sister chromosomes. In the absence of certain membrane proteins, cells grow instead as large, multichromosomal spheres that divide successively in planes that are at right angles to one another. Although multichromosomal, the spherical cells cannot be maintained as heterozygotes. These observations imply that, in these mutants, each individual chromosome g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
2
23
1
Order By: Relevance
“…If cell division is resumed, daughter cells are generated that are morphologically indistinguishable from the mother filamentous cell. Similarly, resumption of several rounds of cell division in spherical cells yields spheres of unit size (9).…”
Section: Discussionmentioning
confidence: 99%
“…If cell division is resumed, daughter cells are generated that are morphologically indistinguishable from the mother filamentous cell. Similarly, resumption of several rounds of cell division in spherical cells yields spheres of unit size (9).…”
Section: Discussionmentioning
confidence: 99%
“…SHA6 (a rodA (Amber mutant) strain with spherical morphology) carries a duplication of the 0-14 min region of the chromosome which includes the dcw cluster (K. Begg, personal communication; Addinall, 1994;Donachie et al, 1995). In addition, SHA6 carries two functional copies of ftsW (S. G. Addinall, personal communication), therefore, even if ftsW is an essential gene, it should be possible to introduce the ftsW ::cat allele into SHA6 without the need for plasmid-mediated complementation.…”
Section: Identification Of the Promoter Region For Ftswmentioning
confidence: 99%
“…The round mutant (rodA) and its parental rod-shaped cell were obtained from K. Begg (9). Any discrepancies between previous work with this mutant and the results reported here are therefore not due to genetic differences.…”
mentioning
confidence: 72%
“…This indicates that there is no major reorganization of the division process in the round mutant. Donachie et al (9) had previously concluded that in the round mutant successive planes of division occur at right angles to each other.…”
mentioning
confidence: 98%
See 1 more Smart Citation